Safety and efficacy of elbasvir/grazoprevir for the treatment of chronic hepatitis C: current evidence - Morikawa K; Nakamura A; Shimazaki T; Sakamoto N (Dove Medical Press, 2018)
Kenichi Morikawa, Akihisa Nakamura, Tomoe Shimazaki, Naoya Sakamoto Department of Gastroenterology and Hepatology, Hokkaido University Faculty of Medicine and Graduate School of Medicine, Sapporo, Japan Abstract: Treatments for hepatitis C virus (HCV) have advanced greatly, becoming more efficacious with fewer adverse events, due to the availability of direct-acting antiviral agents, which target specific steps in the HCV life cycle. Recently, a combination regimen consisting of the HCV nonstructural protein 5A inhibitor elbasvir (EBR) and the HCV NS3/4A protease inhibitor grazoprevir (GZR) was approved for the treatment of patients with chronic HCV and genotypes (Gts) 1 and 4 in various countries. In Phase III trials, the combination of EBR/GZR (fixed-dose combination table or single agent) for 12 or 16 weeks of treatment with or without ribavirin resulted in a high sustained virological response at 12 weeks in treatment-naïve and treatment-experienced patients with HCV Gt 1a, 1b, 4, or 6, including special populations, such as individuals with advanced chronic kidney disease, HCV-HIV coinfection, and compensated cirrhosis. In this review, we focus on the mode of action, pharmacokinetics, clinical applications, efficacy, and safety profile of EBR/GZR, including special populations who have been considered refractory from the extensive evidence of clinical trials. Keywords: HCV, DAAs, compensated LC, HCV/HIV